Methodology for mapping the distribution of altitudinal wetland forests in the Brazilian Semiarid - Ramos, Renilson Pinto da Silva; Souza, Bartolomeu Israel de; Lucena, Daisy Beserra (Geografia Ensino & Pesquisa, 2020)
Altitudinal Wetland Forests are fields with humid and subhumid climates located in the interior of the Brazilian semiarid that are linked to the climate past of this region. This dry climate domain region has high importance due to both the presence of paleoclimate remnants and its developed economy. The purpose of this work was to try to indicate through mapping, beyond what is officially known, new areas that may include Altitudinal Wetland Forests. The methodology developed was based on using computational techniques in a GIS environment with analysis of hierarchical processes using the altitude variables, rainfall and vegetation in the distribution of Altitudinal Wetland Forests throughout the Brazilian semiarid. It was possible to indicate new areas with high and low probabilities of the occurrence of Altitudinal Wetland Forests, beyond those without any probability. The obtained results indicate that investigations should be carried out to confirm the results of this study and to provide information for interventions in these areas, both from the environmental point of view and for its sustainable agricultural use.